Relevance of the scaphoid shift test for the investigation of scapholunate ligament injuries - Schmauß, Daniel; Pöhlmann, Sebastian; Weinzierl, Andrea; Schmauss, Verena; Moog, Philipp; Germann, Günter; Bickert, Berthold; Megerle, Kai (Journal of Clinical Medicine, 2022)
Background: Although it is part of the common clinical examination of scapholunate ligament pathologies, there are only little data on the diagnostic value of the scaphoid shift test. The aim of this study was to evaluate the scaphoid shift test in a large cohort of patients. Materials and Methods: We retrospectively analysed 447 patients who underwent the scaphoid shift test and wrist arthroscopy because of various suspected injuries of the wrist, correlating the results of clinical examination with data obtained during the wrist arthroscopy. Sensitivity, specificity, and positive and negative predictive values were calculated and evaluated. Results: The sensitivity of the scaphoid shift test was low (0.50) when examining the whole cohort. In a subgroup of patients specifically referred for suspected scapholunate ligament injury, the sensitivity was higher (0.61), but the specificity was low (0.62). In detecting more serious lesions (Geissler 3 + 4), the scaphoid shift test demonstrated higher sensitivity (0.66). Conclusions: An isolated scaphoid shift test may only be of limited value in the diagnosis of scapholunate ligament lesions and should, therefore, be viewed as a useful tool for a preliminary assessment, but a negative test should not prevent the surgeon from indicating a more extensive diagnostic workup.